Titanium alloy lubricating coating as well as preparation method and application thereof

By forming a coating structure of nitriding layer, titanium nitride layer and molybdenum disulfide layer on the TC4 titanium alloy substrate, the problems of high friction noise and high wear rate during the friction process are solved, and the effects of increasing hardness, reducing friction coefficient and extending service life are achieved.

CN119800356APending Publication Date: 2025-04-11YANTAI ADVANCED MATERIALS & GREEN MFG SHANDONG PROVINCIAL LAB +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510036892.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

TC4 titanium alloy has problems such as high friction noise and high wear rate during the friction process, resulting in insufficient load-bearing capacity in actual applications.

Method used

The nitriding layer is formed by ionic nitriding on the surface of the titanium alloy substrate, followed by cathodic arc ion plating to deposit the titanium nitride layer, and electrophoreically depositing the molybdenum disulfide layer on the surface of the titanium nitride layer to prepare a titanium alloy lubricating coating.

Benefits of technology

It improves the hardness and elastic modulus of titanium alloy, enhances the storage capacity of the lubricating phase, significantly reduces the friction coefficient and wear rate, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800356A_ABST
    Figure CN119800356A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of titanium alloys, and particularly relates to a titanium alloy lubricating coating as well as a preparation method and application thereof. The preparation method of the titanium alloy lubricating coating comprises the following steps: carrying out ion nitriding on the surface of a titanium alloy matrix to form a nitriding layer; performing cathode arc ion plating on the surface of the nitriding layer to deposit a titanium nitride layer; and a molybdenum disulfide layer is subjected to electrophoretic deposition on the surface of the titanium nitride layer, and the titanium alloy lubricating coating is obtained. According to the method, after TiN is deposited through plasma nitriding and cathode arc ion plating, a gradient tough sub-layer is formed, the surface hardness and the elastic modulus of the gradient tough sub-layer are improved, and therefore the surface bearing capacity is improved; and then the lubricating sub-layer is constructed on the basis of the tough sub-layer through the electrophoretic deposition technology, the friction coefficient is reduced, and the service life of the titanium alloy lubricating coating is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloys, and in particular relates to a titanium alloy lubricating coating and a preparation method and application thereof. Background Art

[0002] Titanium alloys have many excellent characteristics, such as low density, high specific strength, excellent biocompatibility, corrosion resistance, fatigue resistance and creep resistance, etc. Therefore, they are widely used in metallurgy, construction, petrochemical, aerospace, biological devices, marine measurement and living utensils.

[0003] However, titanium alloys such as TC4 titanium alloy also have some problems, such as poor mechanical properties (low hardness and elastic modulus) leading to insufficient load-bearing capacity, and then large friction noise and high wear rate during the friction process, which affect its use in practical applications. In applications involving surface engineering, due to poor mechanical properties, excessive friction and wear may cause TC4 titanium alloy workpieces to fail. How to improve the wear resistance of titanium alloys and reduce their friction coefficient is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of this, the present invention provides a titanium alloy lubricating coating and a preparation method and application thereof. The titanium alloy lubricating coating prepared according to the method provided by the present invention has higher hardness, elastic modulus and stronger lubricating phase storage capacity, thereby having good wear resistance.

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a titanium alloy lubricating coating, comprising the following steps:

[0006] Ion nitriding is performed on the surface of the titanium alloy substrate to form a nitriding layer;

[0007] Depositing a titanium nitride layer by cathode arc ion plating on the surface of the nitriding layer;

[0008] A molybdenum disulfide layer is electrophoretically deposited on the surface of the titanium nitride layer to obtain the titanium alloy lubricating coating.

[0009] Preferably, the ion nitriding comprises the following steps:

[0010] The titanium alloy substrate is placed in a glow ion nitriding furnace, evacuated, heated, and introduced with nitrogen and hydrogen to perform ion nitriding.

[0011] Preferably, the conditions for ion nitriding include: temperature of 750-850° C., nitrogen flow rate of 15-30 sccm, hydrogen flow rate of 5-10 sccm, plasma RF power of 50-300 W, and time of 250-300 min.

[0012] Preferably, the conditions for the cathode arc ion plating include: the working gas is nitrogen, the working target is a titanium arc target, the bias voltage is -40 to -150 V, the arc current is 220 to 260 A, and the deposition time is 30 to 90 min.

[0013] Preferably, the cathodic arc ion plating deposition includes a first deposition and a second deposition performed sequentially, the bias voltage of the first deposition is -40 to -60 V, and the time of the first deposition is 10 to 20 min; the bias voltage of the second deposition is -120 to -150 V, and the time of the second deposition is 20 to 70 min.

[0014] Preferably, the electrophoretic deposition electrophoretic solution is a mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide, and the electrophoretic deposition time is 5 to 15 minutes.

[0015] Preferably, in the mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide, the mass concentration of molybdenum disulfide is 1-2 g / L, and the mass concentration of hexadecyltrimethylammonium bromide is 0.5-1 g / L.

[0016] The present invention also provides a titanium alloy lubricating coating prepared by the preparation method described in the above technical solution, comprising a titanium alloy substrate and a composite coating coated on the surface of the titanium alloy substrate;

[0017] The composite coating comprises a nitriding layer, a titanium nitride layer and a molybdenum disulfide layer stacked in sequence, and the nitriding layer is in direct contact with the titanium alloy substrate.

[0018] Preferably, the thickness of the nitriding layer is 30-100 μm, and the hardness of the nitriding layer is 8-12 GPa; the thickness of the titanium nitride layer is 2-6 μm, and the hardness of the titanium nitride layer is 18-24 GPa; the thickness of the molybdenum disulfide layer is 4-6 μm.

[0019] The present invention also provides the use of the titanium alloy lubricating coating described in the above technical solution in the preparation of wear-resistant components.

[0020] The present invention provides a method for preparing a titanium alloy lubricating coating, comprising the following steps: performing ion nitriding on the surface of a titanium alloy substrate to form a nitriding layer; performing cathode arc ion plating on the surface of the nitriding layer to deposit a titanium nitride layer; and electrophoretically depositing a molybdenum disulfide layer on the surface of the titanium nitride layer to obtain the titanium alloy lubricating coating. The present invention forms a gradient nitriding transition layer after ion nitriding, realizes a smooth transition of microhardness from the inside of the substrate to the surface of the substrate, reduces stress concentration between the substrate and the titanium nitride layer subsequently deposited by cathode arc ion plating, and enhances the bonding strength of the titanium nitride layer; on the other hand, the presence of the high-hardness titanium nitride layer reduces the removal rate of the molybdenum disulfide lubricating phase on the wear mark, effectively extending the service life of the wear-resistant and lubricating integrated coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The XRD spectrum of TC4 with a nitrided layer prepared in Examples 1 to 3;

[0022] Figure 2 A bar chart comparing the hardness and elastic modulus of TC4 with a nitrided layer prepared in Examples 1 to 3;

[0023] Figure 3 A columnar comparison chart of the hardness and elastic modulus of the TC4 formed with the titanium nitride layer and the TC4 alloy substrate prepared in Examples 1 to 3;

[0024] Figure 4 A bar graph comparing the wear rates of the TC4 formed with the titanium nitride layer and the TC4 alloy substrate prepared in Examples 1 to 3;

[0025] Figure 5 The friction curves of TC4 with lubricating coating prepared in Examples 1 to 3;

[0026] Figure 6 This is the friction curve of TC4 formed with a molybdenum disulfide layer prepared in Comparative Example 1. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a titanium alloy lubricating coating, comprising the following steps:

[0028] Ion nitriding is performed on the surface of the titanium alloy substrate to form a nitriding layer;

[0029] Depositing a titanium nitride layer by cathode arc ion plating on the surface of the nitriding layer;

[0030] A molybdenum disulfide layer is electrophoretically deposited on the surface of the titanium nitride layer to obtain the titanium alloy lubricating coating.

[0031] The present invention performs ion nitriding on the surface of a titanium alloy substrate to form a nitrided layer. As a specific embodiment of the present invention, the ion nitriding may include the following steps:

[0032] The titanium alloy substrate is placed in a glow ion nitriding furnace, evacuated, heated, and introduced with nitrogen and hydrogen to perform ion nitriding.

[0033] As a specific embodiment of the present invention, the titanium alloy matrix may include TA1, TA2, TA3, TA7, TA9, TA10, TC4, TC4ELI, TC6, TC9, TC10, TC11, TB2, TB3, TB4 or TB5.

[0034] As a specific embodiment of the present invention, placing the titanium alloy substrate in front of the glow ion nitriding furnace may also include: ultrasonically washing the titanium alloy substrate and then drying it; the ultrasonic washing may include water ultrasonic washing, acetone ultrasonic washing and anhydrous ethanol ultrasonic washing in sequence; the water used for the water ultrasonic washing may be deionized water; the time for the water ultrasonic washing may be 8 to 12 minutes, the time for the acetone ultrasonic washing may be 8 to 12 minutes, and the time for the anhydrous ethanol ultrasonic washing may be 8 to 12 minutes. The present invention has no special limitation on the drying, as long as the solvent on the surface of the product can be removed.

[0035] As a specific implementation of the present invention, the vacuum degree after evacuation can be 0.5-30Pa.

[0036] As a specific embodiment of the present invention, the conditions of the ion nitriding may include: a temperature of 750-850°C, a nitrogen flow rate of 15-30sccm, a hydrogen flow rate of 5-10sccm, a plasma RF power of 50-300W, and a time of 250-300min; the conditions of the ion nitriding may also be: a temperature of 800°C, a nitrogen flow rate of 20-25sccm, a hydrogen flow rate of 5-8sccm, a plasma RF power of 100-200W, and a time of 270-280min. In the present invention, the heating rate to the temperature required for the ion nitriding may be 8-12°C / min, and may be specifically 10°C / min.

[0037] As a specific implementation of the present invention, the ion nitriding may be further cooled; the temperature of the product after the cooling may be 20-40° C.; the cooling method may be furnace cooling.

[0038] After the nitriding layer is formed, the present invention deposits a titanium nitride layer on the surface of the nitriding layer by cathode arc ion plating. As a specific embodiment of the present invention, before depositing the titanium nitride layer by cathode arc ion plating, it may also include: ultrasonically washing the titanium alloy forming the nitriding layer and then vacuum drying; the ultrasonic washing may include water ultrasonic washing, acetone ultrasonic washing and anhydrous ethanol ultrasonic washing in sequence; the water used for the water ultrasonic washing may be deionized water; the time for the water ultrasonic washing may be 8 to 12 minutes, the time for the acetone ultrasonic washing may be 8 to 12 minutes, and the time for the anhydrous ethanol ultrasonic washing may be 8 to 12 minutes. The present invention has no special requirements for the vacuum drying, and the conventional method in the art may be used.

[0039] As a specific embodiment of the present invention, the conditions of the cathode arc ion plating may include: the working gas is nitrogen, the flow rate of the nitrogen is 600sccm, the working target is a titanium arc target, the bias voltage is -40 to -150V, the arc current is 220 to 260A, and the deposition time is 30 to 90min; the cathode arc ion plating deposition may include a first deposition and a second deposition performed in sequence, the bias voltage of the first deposition may be -40 to -60V, and the time of the first deposition may be 10 to 20min; the bias voltage of the second deposition may be -120 to -150V, and the time of the second deposition may be 20 to 70min. In the initial stage of cathode arc ion plating deposition, the present invention deposits at a relatively low bias voltage (-40V), and the energy of the particles is relatively low, which can avoid excessive bombardment of the substrate surface, thereby reducing substrate damage; and during the initial deposition, the relatively low energy Ti and N ions can gradually fill the microscopic defects on the substrate surface, thereby improving the bonding strength of the coating. Deposition at a higher bias voltage (-150V) in the later stage of cathodic arc ion plating will accelerate the bombardment of Ti and N ions, making the compaction degree between the deposited coating particles higher, reducing pores and defects, improving the density of the coating, and helping to improve the surface hardness and wear resistance of the alloy.

[0040] As a specific embodiment of the present invention, the cathode arc ion plating titanium nitride layer can be cooled after deposition; the temperature of the product after cooling can be room temperature, and the room temperature is 20 to 40°C, and can also be 25 to 35°C; the cooling method can be furnace cooling.

[0041] After obtaining the titanium nitride layer, the present invention electrophoretically deposits a molybdenum disulfide layer on the surface of the titanium nitride layer to obtain the titanium alloy lubricating coating. As a specific embodiment of the present invention, the electrophoretic liquid for electrophoretic deposition can be a mixed solution of molybdenum disulfide (MoS2) and hexadecyltrimethylammonium bromide (CTAB), and the mass concentration of molybdenum disulfide in the mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide can be 1-2 g / L, or 1.5-1.8 g / L; the mass concentration of hexadecyltrimethylammonium bromide in the mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide can be 0.5-1 g / L, or 0.5-0.8 g / L. As a specific embodiment of the present invention, the time of the electrophoretic deposition can be 5-15 min, or 10-13 min.

[0042] As a specific embodiment of the present invention, after the electrophoretic deposition, the electrophoretic deposition product can be dried; the drying can be vacuum drying. The present invention has no special requirements for the vacuum drying, as long as the solvent on the alloy surface can be removed.

[0043] The present invention performs ion nitriding on the surface of the titanium alloy to obtain a strong and tough sublayer that is harder than the titanium alloy substrate, and then performs cathode arc ion plating to deposit a titanium nitride layer to obtain a strong and tough layer that is harder than the nitrided layer, which together constitute a gradient strong and tough sublayer. The formed composite layer can greatly improve the load-bearing capacity of the titanium alloy, achieve a smooth transition of the mechanical properties of the coating from the strong and tough sublayer, and form a gradient structure. Electrophoretic deposition is performed on the basis of the strong and tough sublayer to construct a lubricating sublayer, aiming to reduce its noise during friction and significantly reduce the wear rate. The interface structure and mechanical adaptability between the strong and tough sublayer and the titanium alloy substrate, and the strong and tough-lubricating sublayer ensure the bonding strength between the coating and the substrate, reduce the removal rate of the molybdenum disulfide lubricating phase on the wear mark, and effectively extend the service life of the wear-resistant and lubricating integrated coating.

[0044] The present invention also provides a titanium alloy lubricating coating prepared by the preparation method described in the above technical solution, comprising a titanium alloy substrate and a composite coating coated on the surface of the titanium alloy substrate;

[0045] The composite coating comprises a nitriding layer, a titanium nitride layer and a molybdenum disulfide layer stacked in sequence, and the nitriding layer is in direct contact with the titanium alloy substrate.

[0046] As a specific embodiment of the present invention, the titanium alloy matrix may include TA1, TA2, TA3, TA7, TA9, TA10, TC4, TC4ELI, TC6, TC9, TC10, TC11, TB2, TB3, TB4 or TB5.

[0047] As a specific embodiment of the present invention, the thickness of the nitriding layer can be 30 to 100 μm; the thickness of the titanium nitride layer can be 2 to 6 μm, or 3 to 5 μm; the hardness of the nitriding layer can be 8 to 12 GPa, or 9.86 to 10.95 GPa; the thickness of the molybdenum disulfide layer can be 4 to 6 μm, or 5 μm; the hardness of the titanium nitride layer can be 18 to 24 GPa, or 19.53 to 23.28 GPa.

[0048] The present invention also provides the use of the titanium alloy lubricating coating in the above technical solution in the preparation of wear-resistant components. As a specific embodiment of the present invention, the wear-resistant component is a precision part with good wear resistance, low friction coefficient and low noise.

[0049] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] Example 1

[0051] Ti6Al4V (TC4) was used as a titanium alloy substrate. The TC4 substrate was first ultrasonically cleaned with deionized water for 10 minutes and then ultrasonically cleaned with acetone and anhydrous ethanol as detergents for 10 minutes respectively. After drying, it was placed in a plasma glow nitriding furnace and evacuated to a vacuum degree of 10Pa. The temperature was then raised from room temperature to 800°C at a heating rate of 10°C / min. Nitrogen with a flow rate of 15sccm and hydrogen with a flow rate of 5sccm was introduced. The plasma radio frequency power supply was turned on to perform ion nitriding at 50W. After the nitriding process was completed, the furnace was cooled to 30°C to obtain TC4 with a nitrided layer, which was recorded as 1 (50w).

[0052] The TC4 with nitrided layer was ultrasonically cleaned with deionized water for 10 min, and then ultrasonically cleaned with acetone and anhydrous ethanol as detergents for 10 min respectively; after vacuum drying, it was placed in an ion vacuum coating equipment and evacuated to 8×10 -3 After Pa, high-purity argon was introduced at 600 sccm, and cleaning was completed at -1100V bias for 35 minutes. After cleaning, 240 sccm nitrogen was introduced, and TiN was deposited at -40V bias for the first 10 minutes (with titanium arc target as the working target, arc current of 240A), and TiN was deposited at -150V bias for the next 50 minutes (with titanium arc target as the working target, arc current of 240A). The furnace was cooled to room temperature (30°C) to obtain TC4 with a titanium nitride layer, which was recorded as 1(50w)-TiN;

[0053] The TC4 forming the titanium nitride layer was placed in a mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide (MoS2 mass concentration was 1.5 g / L, CTAB mass concentration was 0.5 g / L) and electrophoretic deposition was performed for 10 minutes. After the electrophoresis was completed, the sample was taken out and dried in a vacuum drying oven to obtain TC4 with a lubricating coating, which was recorded as 1(50w)-TiN-MoS2.

[0054] Example 2

[0055] Ti6Al4V (TC4) was used as a titanium alloy substrate. The TC4 substrate was first ultrasonically cleaned with deionized water for 10 minutes and then ultrasonically cleaned with acetone and anhydrous ethanol as detergents for 10 minutes respectively. After drying, the substrate was placed in a plasma glow nitriding furnace and evacuated to a vacuum degree of 10 Pa. The temperature was then raised from room temperature to 800°C at a heating rate of 10°C / min. Nitrogen gas with a flow rate of 15sccm and hydrogen gas with a flow rate of 5sccm were introduced. The plasma RF power supply was turned on for 0 to 240 minutes to control the plasma RF power supply power to 50W, and the plasma RF power supply power was adjusted to 150W for 240 to 270 minutes. After the nitriding process was completed, the substrate was cooled to 30°C with the furnace to obtain a TC4 with a nitrided layer, which was recorded as 2 (150w).

[0056] The TC4 with nitrided layer was ultrasonically cleaned with deionized water for 10 min, and then ultrasonically cleaned with acetone and anhydrous ethanol as detergents for 10 min respectively; after vacuum drying, it was placed in an ion vacuum coating equipment and evacuated to 8×10 -3 After Pa, high-purity argon was introduced at 600 sccm, and cleaning was completed for 35 minutes at a bias of -1100 V. After cleaning, 240 sccm nitrogen was introduced, and TiN was deposited at a bias of -40 V for the first 10 minutes (with a titanium arc target as the working target, and an arc current of 240 A), and then TiN was deposited at a bias of -150 V for the next 50 minutes (with a titanium arc target as the working target, and an arc current of 240 A). The furnace was cooled to room temperature (30°C) to obtain TC4 with a titanium nitride layer, which was recorded as 2(150w)-TiN;

[0057] The TC4 forming the titanium nitride layer was placed in an electrophoretic solution of a mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide (MoS2 mass concentration is 1.5 g / L, CTAB mass concentration is 0.5 g / L) and electrophoretic deposition was carried out for 10 minutes. After the electrophoresis was completed, the sample was taken out and dried in a vacuum drying oven to obtain TC4 with a lubricating coating, which was recorded as 2(150w)-TiN-MoS2.

[0058] Example 3

[0059] Ti6Al4V (TC4) was used as a titanium alloy substrate. The TC4 substrate was first ultrasonically cleaned with deionized water for 10 minutes and then ultrasonically cleaned with acetone and anhydrous ethanol as detergents for 10 minutes respectively. After drying, the substrate was placed in a plasma glow nitriding furnace and evacuated to a vacuum degree of 10 Pa. The temperature was then raised from room temperature to 800°C at a heating rate of 10°C / min. Nitrogen gas with a flow rate of 15sccm and hydrogen gas with a flow rate of 5sccm were introduced. The plasma RF power was turned on for 0 to 240 minutes to control the plasma RF power to 50W, and the plasma RF power was adjusted to 300W for 240 to 270 minutes. After the nitriding process was completed, the substrate was cooled to 30°C with the furnace to obtain a TC4 with a nitrided layer, which was recorded as 3 (300w).

[0060] The TC4 with nitrided layer was ultrasonically cleaned with deionized water for 10 min, and then ultrasonically cleaned with acetone and anhydrous ethanol as detergents for 10 min respectively; after vacuum drying, it was placed in an ion vacuum coating equipment and evacuated to 8×10 -3After Pa, high-purity argon was introduced at 600 sccm, and cleaning was completed at -1100V bias for 35 minutes. After cleaning, 240 sccm nitrogen was introduced, and TiN was deposited at -40V bias for the first 10 minutes (with titanium arc target as the working target, arc current of 240A), and TiN was deposited at -150V bias for the next 50 minutes (with titanium arc target as the working target, arc current of 240A). The furnace was cooled to room temperature (30°C) to obtain TC4 with a titanium nitride layer, recorded as 3(300w)-TiN;

[0061] The TC4 forming the titanium nitride layer was placed in an electrophoretic solution of a mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide (MoS2 mass concentration is 1.5 g / L, CTAB mass concentration is 0.5 g / L) and electrophoretic deposition was carried out for 10 minutes. After the electrophoresis was completed, the sample was taken out and dried in a vacuum drying oven to obtain TC4 with a lubricating coating, which was recorded as 3(300w)-TiN-MoS2.

[0062] Comparative Example 1

[0063] Ti6Al4V (TC4) was used as the titanium alloy substrate. The TC4 substrate was first ultrasonically cleaned with deionized water for 10 minutes and then ultrasonically cleaned with acetone and anhydrous ethanol as detergents for 10 minutes respectively; after drying, it was placed in an electrophoresis liquid of a mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide (MoS2 mass concentration is 1.5 g / L, CTAB mass concentration is 0.5 g / L) for electrophoretic deposition for 10 minutes. After the electrophoresis is completed, the sample was taken out and dried in a vacuum drying oven to obtain TC4 with a molybdenum disulfide layer, which was recorded as TC4-MoS.

[0064] The TC4 with nitriding layer prepared in Examples 1 to 3 was subjected to X-ray diffraction detection to obtain an XRD spectrum, as shown in FIG. Figure 1 As shown. Figure 1 It can be seen that TC4 has been successfully nitrided to generate a nitride phase (mainly Ti2N phase, containing a small amount of TiN phase).

[0065] The performance of the TC4 formed with a nitriding layer and the TC4 formed with a titanium nitride layer prepared in Examples 1 to 3 and the TC4 alloy substrate were tested according to the following method. Specifically, the nanomechanical properties of different samples were analyzed by using a nanoindenter and a TriboIndenter in-situ nanomechanical detection system manufactured by Hysitron, an American company, to obtain parameters such as plasticity (elastic modulus) and nanohardness. The friction test was completed by a friction tester, and the cross-sectional area of ​​the wear scar was measured by a Leica true color confocal microscope, and the wear rate was calculated. The results are listed in Table 1. According to the above method, the hardness of the titanium alloy substrate TC4 used in Examples 1 to 3 was 3.9 GPa, the elastic modulus was 102.63 GPa, and the wear rate was 823×10 6 mm 3 ·N -1 ·m -1 .

[0066] Table 1 Hardness, elastic modulus and wear rate of TC4 formed with titanium nitride layer prepared in Examples 1 to 3

[0067]

[0068]

[0069] According to Table 1, a columnar comparison chart of the hardness and elastic modulus of TC4 formed into the nitrided layer obtained in Examples 1 to 3 is drawn, as shown in FIG. Figure 2 As shown; according to Table 1, a columnar comparison chart of the hardness and elastic modulus of the TC4 and TC4 alloy substrates formed with the titanium nitride layer prepared in Examples 1 to 3 is drawn, as shown Figure 3 As shown; according to Table 1, a columnar comparison chart of the wear rate of TC4 and TC4 alloy substrates formed with a titanium nitride layer prepared in Examples 1 to 3 is drawn, as shown Figure 4 shown.

[0070] Depend on Figures 2 to 4 It can be seen that the hardness and elastic modulus of TC4 treated by plasma nitriding and arc ion plating TiN deposition are significantly improved, indicating that the bearing capacity of the sample is significantly improved. Among them, 3 (300w) -TiN has the highest hardness and elastic modulus, and 2 (150w) -TiN has the lowest wear rate.

[0071] The friction test was conducted on the TC4 with lubricating coating prepared in Examples 1 to 3 using a friction tester with silicon nitride balls as the friction pair at a speed of 300 rad / min to obtain a friction curve, as shown in FIG. Figure 5 shown.

[0072] A friction test was conducted on the TC4 formed with a molybdenum disulfide layer prepared in Comparative Example 1 using a friction tester with silicon nitride balls as the friction pair at a speed of 300 rad / min to obtain a friction curve, as shown in FIG. Figure 6 shown.

[0073] contrast Figure 5 and Figure 6 It can be seen that after ion nitriding and cathode arc ion plating to deposit TiN, the strong and tough sublayer can provide excellent load-bearing effect, greatly extending the friction life of the MoS2 layer; the TC4 substrate that has not undergone plasma nitriding and cathode arc ion plating to deposit TiN does not have good load-bearing capacity, and the friction life of MoS2 is extremely short.

[0074] The present invention constructs a gradient strong and tough sublayer on the surface of the titanium alloy through ion nitriding and cathode arc ion plating to deposit TiN, and the surface hardness reaches 23GPa and the elastic modulus is increased to a maximum of 328GPa. Compared with the titanium alloy (surface hardness 3.9Gpa, elastic modulus 103GPa), the surface hardness is increased by about 6 times, the Young's modulus is increased by about 3 times, and the surface bearing capacity is improved; then, on the basis of the strong and tough sublayer, a lubricating sublayer (molybdenum disulfide layer) is constructed by electrophoretic deposition technology, which reduces the friction coefficient compared with the untreated titanium alloy and effectively extends the service life of the workpiece; wherein when the friction coefficient is maintained at a minimum of 0.05, the life of each embodiment is: Example 1 is 2245s, Example 2 is 2465s, Example 3 is 2562s, and Comparative Example 1 is 90s.

[0075] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a titanium alloy lubricating coating, characterized in that: The following steps are involved: Ion nitriding is performed on the surface of the titanium alloy substrate to form a nitriding layer; Depositing a titanium nitride layer by cathode arc ion plating on the surface of the nitriding layer; A molybdenum disulfide layer is electrophoretically deposited on the surface of the titanium nitride layer to obtain the titanium alloy lubricating coating.

2. The method for preparing the titanium alloy lubricating coating according to claim 1, characterized in that: The ion nitriding comprises the following steps: The titanium alloy substrate is placed in a glow ion nitriding furnace, evacuated, heated, and introduced with nitrogen and hydrogen to perform ion nitriding.

3. The method for preparing the titanium alloy lubricating coating according to claim 2, characterized in that: The conditions of ion nitriding include: temperature of 750-850° C., nitrogen flow rate of 15-30 sccm, hydrogen flow rate of 5-10 sccm, plasma radio frequency power of 50-300 W, and time of 250-300 min.

4. The method for preparing the titanium alloy lubricating coating according to claim 1, characterized in that: The conditions of the cathode arc ion plating include: the working gas is nitrogen, the working target is a titanium arc target, the bias voltage is -40 to -150 V, the arc current is 220 to 260 A, and the deposition time is 30 to 90 min.

5. The method for preparing the titanium alloy lubricating coating according to claim 4, characterized in that: The cathode arc ion plating deposition includes a first deposition and a second deposition performed sequentially, wherein the bias voltage of the first deposition is -40 to -60 V, and the time of the first deposition is 10 to 20 min; the bias voltage of the second deposition is -120 to -150 V, and the time of the second deposition is 20 to 70 min.

6. The method for preparing the titanium alloy lubricating coating according to claim 1, characterized in that: The electrophoretic deposition electrophoretic solution is a mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide, and the electrophoretic deposition time is 5 to 15 minutes.

7. The method for preparing the titanium alloy lubricating coating according to claim 6, characterized in that: In the mixed solution of molybdenum disulfide and hexadecyltrimethylammonium bromide, the mass concentration of molybdenum disulfide is 1-2 g / L, and the mass concentration of hexadecyltrimethylammonium bromide is 0.5-1 g / L.

8. The titanium alloy lubricating coating prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It comprises a titanium alloy substrate and a composite coating coated on the surface of the titanium alloy substrate; The composite coating comprises a nitriding layer, a titanium nitride layer and a molybdenum disulfide layer stacked in sequence, and the nitriding layer is in direct contact with the titanium alloy substrate.

9. The titanium alloy lubricating coating according to claim 8, characterized in that: The thickness of the nitriding layer is 30-100 μm, and the hardness of the nitriding layer is 8-12 GPa; the thickness of the titanium nitride layer is 2-6 μm, and the hardness of the titanium nitride layer is 18-24 GPa; the thickness of the molybdenum disulfide layer is 4-6 μm.

10. Use of the titanium alloy lubricating coating according to claim 8 or 9 in the preparation of precision parts.